Positive End-Expiratory Pressure as a Factor Influencing Cerebral Perfusion Pressure (an experimental study) - V. E. Leshkova; Sh. V. Timerbulatov; M. A. Sadritdinov; V. M., Sibayev; R. F. Galeyev; B. I. Gimatdinov; R. M. Sakhautdinov (Общая реаниматология)
Objective: to evaluate the effect of positive end-expiratory pressure (PEEP) on cerebral perfusion pressure (CPP) in intracranial hypertension in an experiment using a biological model. Materials and methods. The experiment was carried out on 10 pigs aged 2 months and weighing 17—20 kg. The experimental animals were anesthetized. The authors monitored the following parameters: invasive arterial and central venous pressures, intracranial pressure (ICP), and peak inspiratory pressure. ICP was simulated with a subdurally placed balloon. During mechanical ventilation (MV), PEEP was gradually increased up to 5, 10, 15, and 20 cm H2O. Results. PEEP elevation during MV was accompanied by a progressive rise in intrathoracic pressure and a reduction in mean blood pressure. When PEEP was increased, there was a significant rise in ICP in the intact brain and basic subcompensated intracranial hypertension; no statistically significant change in ICP was observed in decompensated intracranial hypertension. The safe PEEP with regard to CPP was determined by the severity of basic intracranial distention (it was 15 cm H2O in the intact brain and 10 cm H2O in subcompensated hypertension); PEEP exerted no significant effect on CPP in decompensated intracranial hypertension. Conclusion. The effect of PEEP on CPP is determined by not only the value of PEEP, but also by the severity of brain damage. Key words: positive end-expiratory pressure, intracranial pressure, cerebral perfusion pressure.